Respuesta :
Given equation is :
[tex]2x^{5}+10x^{4}-22x^{3}[/tex]=0
Taking out [tex]2x^{3}[/tex] common we get,
[tex]x^{2}+5x-11[/tex]=0
Now solving this we get,
As 11 is not factor-able, we will solve it using the formula,
[tex]x=\frac{-b+\sqrt{b^{2}-4ac}}{2a}[/tex]
a=1 b=5 and c=-11
we get,
[tex]x=\frac{-5+\sqrt{69} }{2}[/tex] and [tex]x=\frac{-5-\sqrt{69} }{2}[/tex]
Answer:
The factor of [tex]2x^{5} + 10x^{4} - 22x^{3}[/tex] is [tex]2x^{3} ({x^{2}}{} + {5x^{}}} - {11})[/tex]
Step-by-step explanation:
Given:
[tex]2x^{5} + 10x^{4} - 22x^{3}[/tex]
Required:
Factorize
To factor a number means to take the number apart to find its factors
To factor [tex]2x^{5} + 10x^{4} - 22x^{3}[/tex] means we look for factors that can divide individual unit of the algebraic expression to the barest minimum
One factor that can divide through is [tex]2x^{3}[/tex]
We then divide each individual unit of the expression with [tex]2x^{3}[/tex]
So, we write [tex]2x^{5} + 10x^{4} - 22x^{3}[/tex] as
[tex]2x^{3} (\frac{2x^{5}}{2x^{3}} + \frac{10x^{4} }{2x^{3}} -\frac{22x^{3}}{2x^{3}})[/tex]
Divide expression in bracket
[tex]\frac{2x^{5}}{2x^{3}} = \frac{2x^{5-3}}{2}[/tex]
[tex]\frac{2x^{5}}{2x^{3}} ={x^{2}}[/tex]
[tex]\frac{10x^{4} }{2x^{3}} = \frac{10x^{4-3} }{2}[/tex]
[tex]\frac{10x^{4} }{2x^{3}} = \frac{10x}{2}[/tex]
[tex]\frac{10x^{4} }{2x^{3}} = {5x}[/tex]
[tex]\frac{22x^{3}}{2x^{3}} = \frac{22x^{3-3}}{2}[/tex]
[tex]\frac{22x^{3}}{2x^{3}} = \frac{22x^{0}}{2}[/tex]
[tex]\frac{22x^{3}}{2x^{3}} = \frac{22 * 1}{2}[/tex]
[tex]\frac{22x^{3}}{2x^{3}} = 11[/tex]
Bringing these results together, we have
[tex]2x^{3} (\frac{2x^{5}}{2x^{3}} + \frac{10x^{4} }{2x^{3}} -\frac{22x^{3}}{2x^{3}})[/tex] = [tex]2x^{3} ({x^{2}}{} + {5x^{}}} - {11})[/tex]
Hence the factor of [tex]2x^{5} + 10x^{4} - 22x^{3}[/tex] is [tex]2x^{3} ({x^{2}}{} + {5x^{}}} - {11})[/tex]